#### Answer

$\dfrac{2x}{y^2}\sqrt[5]{\dfrac{x}{y}}$

#### Work Step by Step

Using the properties of radicals, the given expression, $
\sqrt[5]{\dfrac{32x^6}{y^{11}}}
,$ simplifies to
\begin{array}{l}\require{cancel}
\dfrac{\sqrt[5]{32x^6}}{\sqrt[5]{y^{11}}}
\\\\=
\dfrac{\sqrt[5]{32x^5\cdot x}}{\sqrt[5]{y^{10}\cdot y}}
\\\\=
\dfrac{\sqrt[5]{(2x)^5\cdot x}}{\sqrt[5]{(y^{2})^5\cdot y}}
\\\\=
\dfrac{2x\sqrt[5]{x}}{y^{2}\sqrt[5]{y}}
\\\\=
\dfrac{2x}{y^2}\sqrt[5]{\dfrac{x}{y}}
\end{array}
* Note that it is assumed that all variables represent positive numbers.